Development and application of an integrated system of dewatering and recharge for the deep foundation pit - Zhenjie Zhang; Chunpin Zeng; Enzhong Zhang; Qingwei Su; Min Li; Liang Gong; Fuqiang Geng; Zhigang Zhang (Applied Water Science, 2023)
Abstract A large amount of pumping in the deep foundation pit will reduce the groundwater level and lead to surface cracking, building settlement, ground collapse and spring water cut-off. And the groundwater recharge is a good control measure. An integrated system of dewatering and recharge for the deep foundation pit is developed, and it is mainly composed of a pumping system, an assembled water tank, a variable frequency pressure system, a cleaning and filtering system, a recharge pressure tank, a recharge well system and a central control system. This system can realize intelligent automatic control according to the monitoring data. It does not require staff to operate on site and can be remotely adjusted by computer or mobile phone. Taking a subway station under construction in Jinan as the background, the single well recharge test and the multiple wells recharge test were carried out. It can be found that with the increase of recharge pressure, the recharge volume gradually increases, but the increasing trend is smaller and smaller. The relationship between the groundwater level and the recharge volume is a logarithmic function. Blindly increasing recharge wells may not improve the overall reinjection volume, and the relationship between the number of recharge wells, the diameter of reinjection pipes and the maximum recharge capacity of the variable frequency pressure system needs to be comprehensively considered.